Persepsi Pemangku Kepentingan terhadap Partisipasi Masyarakat dalam Pembangunan Desa Sekitar Tambang - Muhammad Ihsan Mattalitti (LP3M Universitas Muhammadiyah Kendari, 2022)
This study aims to present the results of a case study on stakeholders' perceptions of community participation in village development activities around mining area in a village in Central Sulawesi. Data were collected from 12 participants through in-depth interviews. Using content analysis and community participation in development as analytical framework, the results of data analysis depict that the community acknowledges the village government’s various efforts to encourage community participation through community development and community involvement in village development. However, the community involvement in village development is still lacking due to limited villagers’ participation. One of the reliant factors for the low participation is because most of the residents are mining workers.